DNA methylation and transcriptome comparative analysis for Lvliang Black goats in distinct feeding pattern reveals epigenetic basis for environment adaptation. Issue 1 (1st January 2021) - Wang, Xi; Li, Xi; Wu, Sujun; Shi, Kerong; He, Yanghua
Abstract: Different feeding patterns exhibit completely different and heritable growth properties in livestock, but the underlying epigenetic mechanisms remain unclear. Here, we investigated genome-wide DNA-methylation and gene expression under grazing and confinement regimen feeding strategies with Lvliang Black goat. We identified 102 differently expressed genes and 7, 833 differentially methylated regions (DMRs) between the two groups. Integrating DNA-methylation and gene expression showed that genes in DMRs exhibit significantly different expression level (FDR < 0.05). KEGG pathway analysis indicated that most of the genes involved in environment adaptation pathways like lipid transpor and metabolism immunity. In sum, our data provided insight into the epigenetic mechanism underlying growth property difference resulting from distinct feeding patterns in goat, and also offered theoretical basis for the rational utilization of germplasm resources of local breeds. Supplemental data for this article is available online at https://doi.org/10.1080/13102818.2021.1914164 .